Postcolonial images studies in North African film - Armes, Roy 1937- (Indiana University Press, 2005)
Roy Armes examines the political & cultural context of the films & the film industry of the Maghreb in the era since independence. Included is a detailed examination of ten films made in Algeria, Morocco & Tunisia between 1970 & 2000.
Includes bibliographical references and index
Keywords: Geschichte 1965-2002; Cinéma - Afrique du Nord; Filmkunst; Postkolonialisme; Film; aMotion pictures -- zAfrica, North; Nordafrika